Strengthening Digital Literacy to Prevent Online Gambling Exposure through Social Media among Adolescents in Terasa Village, Sinjai Regency - Nur Azizah Eka Budiarti; Haekal Febriansyah Ramadhan; Dewi Fatmarani Surianto; Rahmaniar; Muhammad Fadhullah (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
The rapid expansion of online gambling in Indonesia has increasingly reached adolescents, largely through advertisements, links, and persuasive content circulating on social media. Adolescents in Terasa Village, Sinjai Regency, are particularly vulnerable because intensive social media use is not yet balanced by adequate digital literacy. This community service activity aimed to strengthen adolescents' digital literacy as a protective strategy to prevent exposure to online gambling through social media. The activity employed a participatory, practice-based training that combined interactive lectures, demonstrations, and simulations, and used a one-group pretest–posttest design to measure changes in participants' understanding. A nine-item instrument covering digital literacy concepts, recognition of online gambling content, its impacts, and reporting procedures was administered before and after the training. The results showed improvement across all items, with the average proportion of correct answers rising from about 60.7% in the pretest to about 89.3% in the posttest, an average increase of roughly 28.6 percentage points. The Normalized Gain value was about 0.73, which falls into the high category. The largest improvement occurred on items concerning how to block and report gambling content, which were initially the least understood. These findings confirm that practice-based digital literacy training is effective in closing knowledge gaps and equipping rural adolescents with protective skills against online gambling exposure.